Identitas nasional di era digital: Membangun kedaulatan budaya di tengah arus globalisasi digital - husada, moch nazar aditia (Maliki Interdisciplinary Journal, 2025)
The flow of globalization marked by the rapid development of technology and information has had a major influence on the social and cultural dynamics of Indonesian society, especially among the younger generation. Easy access to foreign cultures through digital media often makes foreign cultures a role model, which ultimately shifts the nation’s noble values ​​and erodes national identity. This condition raises concerns about a decline in nationalism and a decreasing concern for local culture. In fact, national identity is a fundamental element that characterizes and unites the Indonesian nation in its diversity. Therefore, joint efforts are needed from various parties including the government, educational institutions, the community, and creative industry players to strengthen national identity through the use of digital media. Some strategic steps that can be taken include integrating cultural values ​​into the education system, creating interesting digital content based on local culture, and increasing digital literacy that is oriented towards cultural preservation. In this way, the younger generation is expected to play an active role as guardians and preservers of national culture amidst the rapid flow of globalization, as well as helping to realize Indonesia’s cultural sovereignty in the digital era.